Beyond typologies - alternative ways of comparing VET systems - Fischer, Martin [Verfasser] (My University, 2020)
"Typologies (like 'market system', 'school system' or 'dual-cooperative system' of vocational education and training (VET)) promise to provide a general overview over the main characteristics of a articular VET system. However, comparing VET systems by typologies has been criticised as prejudice-driven because such typologies are often not the result of a comparison between national VET systems but rather their starting point. Moreover, through typologies a unity is assigned to VET systems, which often does not exist in reality. In the paper two other possibilities of comparing VET systems are described and discussed: I) comparison by function and 2) comparison by quality. The first approach is guided by the assumption that VET has (potentially) different functions for the people and the entire society within a country such as the qualification function, the selection of students according to the hierarchy of occupations, the allocation of employees, the utilisation of economic resources and the integration of individuals into society. Following this assumption the question can be answered: How and to which extent are those functions realised through a national VET system? When comparing VET by quality, it is assumed that features ofa VET system can reach a certain quality such as input, process, output and outcome quality. Those dimensions of VET quality can be adapted to different levels of a VET system (micro, meso and macro level) and deliver information about the quality of a VET system as a whole. Advantages and disadvantages of both approaches will be discussed in final part of the paper." (author's abstract ; BIBB-Doku)
Keywords: T 1.5 International vergleichende Berufsbildungsforschung; Vergleichende Berufsbildungsforschung; Berufsbildungssystem; Qualifizierung; Qualität; Funktion